The Reality of Leadership Succession Plans in Government Ministries in Kingdom of Saudi Arabia - Albawrdy, Faisal Abdullah; Alshumailan, Abdulwahab Bin Shabab (The Arab Journal of Administration, 2025)
Objective of the study: To answer the principal question about the reality of leadership succession plans in government ministries in Kingdom of Saudi Arabia. Data collection tool: The questionnaire was used on a sample of 380 managers working in those ministries, of which 288 questionnaires were returned valid for analysis. Most important outputs: The approval of the majority of the study sample on the ministries’ support and interest in leadership succession plans, as the arithmetic mean reached (2.53) out of 4, and the study sample’s low agreement that the ministries are ready to evaluate and identify second-line leaders, the weak use of training and development to build future leaders, and the limited readiness of the ministries to monitor and develop the leadership succession plan, as their averages were (2.45), (2.35), and (2.28), respectively, out of (4). Also, there are statistically significant differences on the axis of the level of support and interest of ministries for leadership succession plans and on the axis of the ministries’ use of a plan to train and develop second-line leaders to provide future leaders according to the level of the job, and on all the axes of the study according to the years of experience. Most Important Recommendations: The necessity of reviewing, revising and developing civil service regulations to support leadership succession plans, the importance of integrating human resources activities with leadership succession and ministries’ strategies, and the need to support leadership succession plans by the ministries.